Changing landscape of liver cirrhosis in multi-racial Asian country: a decade comparison - Nik Muhamad Affendi, Nik Arsyad; Sekaran, Sharini; Azmi, Siti Sholihah; Mohd Mahyudin, Nazlin Adlina; Rajaram, Ruveena Bhavani; Mahadeva, Sanjiv (2022)
BACKGROUND AND AIM: Chronic viral hepatitis B infection was the most common cause of liver cirrhosis in Asian countries, however with the rising prevalence of obesity and implementation of prevention strategies for viral hepatitis B transmission, we predict that there is a change in the epidemiology of liver cirrhosis. Our aim is to determine the change in epidemiology of liver cirrhosis and hepatocellular carcinoma in our centre. METHODS: A cross sectional study was conducted where we recruited all liver cirrhosis patients who were attending inpatient and outpatient service in our centre from July 2019 to July 2021. Baseline demography and clinical characteristics were collected via electronic medical record system. Data collected was analyzed and compared with historical data from our centre that was collected approximately a decade ago, from April 2006 to May 2009. RESULTS: A total of 354 patients were recruited into this study consisting of 198 male (55.9%) and 156 female (44.1%) with mean age of 63.36 year-old (20–90). The aetiologies of liver cirrhosis were NASH, n = 144, (40.7%); viral hepatitis B, n = 78, (22%); viral hepatitis C, n = 31, (8.8%); alcohol, n= 29, (8.2%); viral hepatitis B + NASH, n = 16, (4.5%); cryptogenic, n = 23, (6.5%) and autoimmune hepatitis, n = 11, (3.1%). NASH was the leading ateology in Malay (50.4%) and Indian (46.3%) while viral Hepatitis B was the main aetiology in Chinese (33.3%). 48 patients (13.6%) had hepatocellular carcinoma with viral hepatitis B being the most dominant cause (45.8%) followed by NASH (18.8%) and alcohol (6.3%). CONCLUSION: Our study showed that there was a drastic change in epidemiology of cirrhosis where the predominant aetiology has changed from viral hepatitis B to NASH. However, viral hepatitis B remained the commonest cause of hepatocellular carcinoma followed by NASH.